Dual Synthesisi Of Poly(3- Hydroxybutyrate-Co-4-Hydroxybutyrate) Copolymer And Yello Pigment By Cupriavidus Sp. Usmahm13 And Its Characterization - Ismail, Iszatty (2017)
Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] copolymer has attracted intensive attention in various applications. Cupriavidus sp. USMAHM13 was found to have the ability of producing P(3HB-co-4HB) copolymer and yellow pigmentation simultaneously. Preliminary study had shown that the pigment extract exhibited antimicrobial activity against various bacteria. This present study was first conducted by applying various strategies to evaluate the effect of various carbon precursors on the biosynthesis of P(3HB-co-4HB) and yellow pigment.